Developing The Textbook “Arabic Books by Scientific Approach In Curriculum 2013” Using Mind Mapping (Research and Development For Fourth Grade of MIT Daarut Tahfidz al-Ikhlas) - Nisak, Rahmatun (Asalibuna, 2021)
A textbook is a prominent source to attract student’s attention. Arabic Books by Scientific Approach in Curriculum 2013 is a textbook used in learning Arabic at MIT Daarut Tahfidz al-Ikhlas. However, the researcher found problems experienced by students in learning grammar, they are difficulties in understanding content material, so that make the students in boredom and less enthusiastic in learning. So this research purpose to develop the textbook using the Mind Mapping used in learning Arabic at MIT Daarut Tahfidz al-Ikhlas. This research aims to know the process of developing the textbook “Arabic Books by Scientific Approach in Curriculum 2013” and to know the effectiveness of using a book which has been developed. The researcher using the methodology of scientific research and development (Research & Development / R & D). The data collection consists of direct observation, interview, and test in 24 samples in the fourth-grade students. In the results of the research, the developed textbook with mind mapping was effective in improving the ability of students in learning grammar, the calculated of t-count on the result, as analyzed by the researcher t-test related. The theoretical value (t-table) on the degree of freedom 8 df = and at the level of significance of 5% (0.05 = α) is 1.86.